Petrogenesis and thermal history of the Yulong porphyry copper deposit, Eastern Tibet: insights from U-Pb and U-Th/He dating, and zircon Hf isotope and trace element analysis - Li, J; Qin, K; Li, G; Cao, M; Xiao, B; Chen, L; Zhao, J; Evans, Noreen; McInnes, Brent (Springer, 2012)
The Yulong porphyry copper deposit (6.5 Mt at 0.46 % Cu) in eastern Tibet was formed in a post-collisional setting. New zircon U–Pb and U–Th/He ages, apatite U–Th/He ages and in-situ zircon Hf isotopic and trace element data for the Yulong ore-bearing adakitic porphyries elucidate the thermal history and petrogenesis of the deposit. Zircon U–Pb ages range from from 41.2 Ma to 40.7 Ma, indicating an Eocene formation age. Combined with the zircon U–Th/He age of 37.5 ± 1.2 Ma, results suggest that magmatic-hydrothermal evolution lasted up to 5 m.y. The apatite U–Th/He age of 33.4 ± 0.9 Ma reflects Yulong deposit exhumation during the ~33–30 Ma Tibetan uplift. Moreover, the high εHf(t)-values (7.1 ~ 12.2) zircon yield the highest ΣREE content, higher Y/Hf, lower Ce/Ce* and higher Th/U ratios compared to inherited zircon or magmatic zircon suggesting that the high εHf(t) zircon crystallized from another magma, and that magma mixing probably contributed to the adakitic porphyries at Yulong. In addition, inherited and magmatic zircon with the lowest εHf(t) values (−20.6 ~ −4.4) suggest crustal contamination. The positive zircon εHf(t) values indicate a source in the juvenile arc lower crust. Significantly, the juvenile arc lower crust inherited arc magma characteristics (abundant F, Cl, Cu and high oxidation state), which are now found in the porphyry Cu–Mo deposits.